Molecular Characterisation of Soil-Dwelling Bacillus thuringiensis using Transcriptional Regulator, XRE Gene and the Crystal Protein, cry2 gene - Akinyelure, E. O.; Machido, D. A.; Atta, H. I. (UMYU Journal of Microbiology Research)
Bacillus thuringiensis (Bt) is the organism that is used most frequently in biological pest management, which is distinguished by the capacity to possess crystalline inclusions throughout the sporulation phase. There is an increasing need to use biological control in controlling plant pathogens due to the inherent advantages. However, the detection of Bt has become more time consuming and cumbersome due to the numerous available crystal genes. The goal of the study was to isolate strains of Bacillus thuringiensis from the soil, characterise the isolates using the transcriptional regulator, XRE gene and the crystal proteins cry2gene and compare the efficiency of these two biomarkers in identifying Bt species. Five different Bacillus thuringiensis strains were isolated from soil samples in Zaria, Nigeria. Polymerase chain reaction was used to detect the existence of the cry2 and XRE genes. Four (80%) of the five isolates harboured the XRE genes, while none (0%) harboured the cry2 genes. This observation is a likely indication that the XRE gene is a reliable biomarker in the identification of Bt isolates from environmental samples. In order to ensure speed and reproducibility in the detection of Bt from environmental samples, molecular techniques targeting the XREgene are recommended.